Nanoporous walls on macroporous foam : rational design of electrodes to push areal pseudocapacitance - Guan, Cao (2013)
For application as a pseudocapacitor electrode, highly porous CoO nanowalls are fabricated directly on 3D macroporous nickel foam (see images). A relatively high areal capacitance is achieved because of the porous structure. By grafting the porous nanowalls with another pseudocapacitive oxide, the areal capacitance can be further significantly boosted, owing to the increased surface area caused by the hierarchically porous structure as well as a possible synergetic effect between the two oxides.